Family Function and Academic Achievement: The Mediating Role of Noble Character - Lubis, Rahmi; Tafonao, Lince Kristina; Adawiyah, Zain; Hutagalung, Fonny Dameaty (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2024)
Academic achievement reflects the level of success students achieve in college studies. Based on observation, a prominent factor that typically influence this metric is family roles, particularly through the mediation of noble character. Therefore, this research aims to examine the mediating role of noble character on the relationship between family roles and student academic achievement. In order to achieve the stated objective, 201 college students were selected using cluster stratified random sampling, which served as the sample in this explanatory quantitative research. Accordingly, three key variables observed during the course of the exploration include family function, noble character scales, and student cumulative achievement index. A mediation test was also carried out using Jamovi statistical software 2.0.0 to determine the relationship between the key variables. The obtained results from the test showed that family function did not directly influence educational achievement. Instead, it only determined academic achievement through the instillation of noble character in students. Based on this result, an inference was made that noble character significantly mediated the relationship between family function and academic achievement.